(Invited) An Improved the Impedance Spectroscopy Measurements with Non-Contact Microelectrodes Embedded into a Flexible Polymer Comprising a Microfluidic Network. (5th January 2017) - Kechadi, Mohammed; Chaal, Lila; Tribollet, Bernard; Gamby, Jean
Abstract : Two coplanar carbon microelectrodes were coated with the polymer by using a photoablation procedure in order to avoid any faradic reactions in the fluidic channel. In fact, only the dielectric properties of microelectrodes/ polymer/ fluidic channel interface are taken into consideration. This paper develops an analytical model that permits to predict the best frequency range to be selected for real-time contactless microchannel resistance changes. The non contact electric impedance spectroscopy is promising for new generation of sensor or biosensor applications on miniaturized flexible or patch polymer devices.